2016
DOI: 10.5114/ada.2016.59156
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of mutations in the gene encoding filaggrin in the population of Polish patients with atopic dermatitis

Abstract: IntroductionThe genetic background of atopic dermatitis (AD) is complex, involves many genes and their participation varies in varied populations, and depends on the intensity and course of a disease. Changes in the nucleotide sequence of the FLG gene and a reduced number or a deficit of the functional product of processed profilaggrin can be one of risk factors for atopic dermatitis.AimTo determine the prevalence of R501X and 2282del4 mutations of the FLG gene in patients with AD.Material and methodsThe studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In the European population, the prevalence of FLG gene alterations, especially of R501X and 2282del4 mutations, varies among different regions, depending on the ethnic groups [ 3 , 4 , 5 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the European population, the prevalence of FLG gene alterations, especially of R501X and 2282del4 mutations, varies among different regions, depending on the ethnic groups [ 3 , 4 , 5 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were 2 Polish studies that investigated the association between FLG mutations and AD. 33,34 De z bi nska et al 33 found FLG mutations in 2.8% of healthy subjects and 13.8% in AD patients with mild and moderate AD. Wo zniak et al 34 2282del mutations in 30% of AD patients, while no mutations have been discovered in controls.…”
Section: Discussionmentioning
confidence: 99%
“…There are only limited data about the prevalence of FLG mutations in the countries of East and Southern Europe. There were 2 Polish studies that investigated the association between FLG mutations and AD . Dębińska et al .…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing genetic factors for the development of AD include mutations in genes affecting the integrity of the skin barrier, such as mattrin ( TMEM79 ) and filaggrin (filament aggregation protein, FLG ) . Filaggrin mutations were found in 30% of AD patients in Poland, China (26.0%), and Korea (15.7%), while healthy individuals had none. Importantly, filaggrin expression is downregulated in AD patients independent of their FLG genotype as a consequence of increased type 2 cytokines contributing to the aggravation of disease …”
Section: Introductionmentioning
confidence: 99%